High performance top-gated multilayer WSe2 field effect transistors. (31st October 2017) - Pudasaini, Pushpa Raj; Stanford, Michael G; Oyedele, Akinola; Wong, Anthony T; Hoffman, Anna N; Briggs, Dayrl P; Xiao, Kai; Mandrus, David G; Ward, Thomas Z; Rack, Philip D
Abstract: In this paper, high performance top-gated WSe2 field effect transistor (FET) devices are demonstrated via a two-step remote plasma assisted ALD process. High-quality, low-leakage aluminum oxide (Al2 O3 ) gate dielectric layers are deposited onto the WSe2 channel using a remote plasma assisted ALD process with an ultrathin (∼1 nm) titanium buffer layer. The first few nanometers (∼2 nm) of the Al2 O3 dielectric film is deposited at relatively low temperature (i.e. 50 °C) and remainder of the film is deposited at 150 °C to ensure the conformal coating of Al2 O3 on the WSe2 surface. Additionally, an ultra-thin titanium buffer layer is introduced at the WSe2 channel surface prior to ALD process to mitigate oxygen plasma induced doping effects. Excellent device characteristics with current on–off ratio in excess of 10 6 and a field effect mobility as high as 70.1 cm 2 V –1 s –1 are achieved in a few-layer WSe2 FET device with a 30 nm Al2 O3 top-gate dielectric. With further investigation and careful optimization, this method can play an important role for the realization of high performance top gated FETs for future optoelectronic device applications.